Vulnerability after covid-19 and the response of a developing city : the case of Bogota, Colombia (2020)
This paper analyses the effect of Covid-19 on health and economic indicators of Bogota, the capital of Colombia, and the responses of the local government to ease the economic shock. We highlight the importance of designing policies that adapt to the local context and complement the existing strategies at the national level, and the implementation of ambitious local programs that would be too difficult to execute nationwide. We also emphasize on the benefits on having an ample fiscal space due to the good behavior of previous administrations, allowing the funding of these programs with sustainable debt.